A study of neurological disorders in pregnancy and puerperium - Gupta, Megha; Pradeep, Yashodhara; Singh, Renu; Shrivastava, P. K. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
Background: Neurological diseases contribute to 20% of maternal deaths. The objective of this study was to find the prevalence of primary and secondary neurological disorders in pregnant and postpartum patients, to study their clinical features, feto-maternal outcome and diagnosis using radiological imaging. Methods: This is a prospective cross-sectional study done over a period of 1 year. Pregnant and postpartum women with neurological disorders except eclampsia were enrolled. A total of 100 cases were analysed out of which 92 underwent radiological imaging to confirm diagnosis. Primary outcome in the form of prevalence of neurological disorders and secondary outcome in the form of maternal and foetal outcome was assessed. Results: The prevalence of neurological disorders in pregnancy is 1150/100000 deliveries. 75 cases were classified as primary neurological disorders (prevalence of 862/100000) which included epilepsy, cerebrovascular accidents, CNS infections, neoplasm, neuropathies and miscellaneous. 25 cases were secondary neurological disorders (prevalence of 287/100000) which included hepatic and septic encephalopathy. Among primary disorders the prevalence of cerebrovascular accidents was found to be highest (33.3%) followed by epilepsy (32%) while that among secondary neurological disorder was of Hepatic encephalopathy (92%). Majority (68%) had recovery while 15%of women had residual deficit. There were 17 (17%) cases of maternal mortality. Conclusions: Neurological disorders were significantly associated with poor feto- maternal outcome. Radiological imaging in the form of MRI is an excellent diagnostic tool for confirming diagnosis of neurological disorders.